Modeling habitat suitability of Hippophae rhamnoides L. using MaxEnt under climate change in China: A case study of H. r. sinensis and H. r. turkestanica - He, Xiao-hui; Si, Jian-hua; Zhu, Li; Zhou, Dong-meng; Zhao, Chun-yan; Jia, Bing; Wang, Chun-lin; Qin, Jie; Zhu, Xing-lin (Frontiers in Forests and Global Change, 2023)
Hippophae rhamnoides is widely known for its important ecological, economic, and social benefits. It is known as the pioneer plant of soil and water conservation, with homology in food and medicine. With the climate warming in recent years, the numbers of this species and countries with this plant have decreased steadily. H. r. sinensis and H. r. turkestanica have the widest distribution area in China, which account for more than 90% of the total national Hippophae rhamnoides resources. We firstly screened the presence data and downscale the environment variables (climate and soil) by correlation analysis. Secondly, based on the 232 occurrence data of H. r. sinensis and 10 environmental variables, the 73 occurrence data of H. r. turkestanica and 11 environmental variables, we simulated and predicted their suitable habitats in China, both at the current time and in the 2050S (2041–2060), and analyzed the dominant factors effecting its distribution by using MaxEnt. Finally, we studied the habitat variations and centroid migrations of these subspecies under future climate scenarios using the spatial analysis function of ArcGIS. The results indicated that the area of suitable habitat for H. r. sinensis is much larger than that of H. r. trkestanica in China. The suitable habitat of H. r. sinensis is concentrated in the middle and upper reaches of the Yellow River, mainly distributed in Shaanxi, Shanxi, Sichuan, Qinghai, Gansu, Ningxia, Tibet, and Inner Mongolia, and that of H. r. trkestanica is mainly distributed in Xinjiang and Tibet. The former is mainly affected by bio13 (precipitation of the wettest month), bio11 (mean temperature of the coldest quarte) and bio3 (Isothermality), and the latter is mainly affected by bio13 (precipitation of the wettest month), bio2 (mean diurnal range) and bio15 (precipitation seasonality), and the former is also more stable in the face of future climate change. They are more susceptible to climate than soil in their survival. Although, the two subspecies tend to expand and migrate toward lower latitude under future climate scenarios, there are some differences. H. r. sinensis will migrate westward, while H. r. trkestanica will migrate eastward as a whole. They have a high stability of suitable habitat and are not at risk of extinction in the future. The study’s findings help to clarify the resource reserve of Hippophae rhamnoides L. in China, which will help to guide the protection of wild resources and to popularize artificial planting in suitable areas, and provides scientific basis for the protection of ecological environment.